Cigarette smoke exposure triggers dendritic cell-derived exosome-mediated Th17 and Treg polarization through an autophagy- and necroptosis-associated SIRT1-dependent mechanism in vitro - Luo, Dongling; Liu, Jifeng; Ya, Leilei; Ruan, Chengxuan; Ou, Siyi; Wei, Yiqian; Lin, Qingyun; Huang, Zhaohong; Nong, Kaiwen (Frontiers in Immunology, 2026)
IntroductionBoth Th17/Treg cell imbalance and dendritic cells (DCs) play critical roles in chronic obstructive pulmonary disease pathogenesis from cigarette smoke. Previous studies have shown that DC-derived exosomes (DCexos) can polarize CD4+ T cells toward either Th17 or Treg phenotypes. However, the role of SIRT1 in regulating DCexos-mediated immune responses under cigarette smoke extract (CSE) exposure, and its association with autophagy and necroptosis, remains unclear. In this study, we assessed the expression of silent information regulator 2 homolog 1 (SIRT1), autophagy markers (ATG16L1, LC3B, and p62/SQSTM1), and necroptosis markers (ZBP1, RIPK3, MLKL, Caspase-8, and Caspase-3) in DCs following CSE exposure. Additionally, we evaluated the effect of a SIRT1 activator (SRT1720) on CSE-exposed DCexos and its ability to polarize CD4+ T cells toward Th17 and Treg subsets.MethodsDCs were generated from bone marrow-derived mononuclear cells isolated from C57BL/6J mice and assigned to three groups: control DCs, CSE-exposed DCs, and SRT1720-treated CSE-exposed DCs. The ability of each group’s exosomes to polarize CD4+ T cells was assessed using a mixed lymphocyte reaction (MLR).ResultsSIRT1 expression in CSE-exposed DCs decreased in a time-dependent manner (all p < 0.05). Expression of ATG16L1 and p62 was also reduced, while LC3B expression was increased under CSE-exposed (all p < 0.01). Expression of ZBP1, RIPK3, MLKL, Caspase-8, and Caspase-3 was elevated following CSE exposure (all p < 0.01). Th17 cell frequencies were increased in the CSE-exposed DC-derived exosomes/MLR group compared to the controls (p < 0.01), while Treg frequencies were decreased (p < 0.01). Autophagy could be improved and the necroptosis could be reduced in the SRT1720-treated CSE-exposed DCs (all p < 0.01). Additionally, Th17 cell polarization reduced and Treg cell differentiation increased in the SRT1720-treated CSE-exposed DC-derived exosomes/MLR group compared to the CSE-exposed group (all p < 0.01).ConclusionCSE exposure induces an imbalance in Th17/Treg polarization through a process mediated by DCexos that entails reduced SIRT1 expression, increased necroptosis, and dysregulated autophagy. SIRT1 activation by SRT1720 can attenuate these effects by restoring immune balance and modulating cell death and survival pathways in DCs under CSE exposure.